Study of Physical Traces Toward Activities and Behaviour of Public Open Space Users (Case Study: Merdeka Square of Binjai City) - Novrial; Marina Dwi Avisha (Talenta Publisher, 2019)
Merdeka Square of Binjai City is one of the public open spaces in Binjai City, which has a variety of activities and various types of public open user behavior. Some users of public open space behavior do not use the square facilities by the function of public open spaces. This study aims to identify the physical traces left by the users, to know the activities and behavior of users of Merdeka Square in Binjai City. The method used is a literature study, direct observation accompanied by behavioral mapping and described descriptively with a qualitative approach. The results showed that the behavior of users did not use the facilities in accordance with their functions, such as using a badminton court as a place to play skateboard, and the activities of users who left a physical traces at the Merdeka Square in Binjai City, such as sitting and relaxing in the grass in the middle of the field. The physical traces left by the users of the Merdeka City Square in Binjai, among others, is damage to the grass area in the middle of the field and damaged sidewalk barriers.